Reassessing Marguerite Duras - Carol J. Murphy (Studies in 20th & 21st Century Literature, 2002)
Since her death on March 3, 1996, Marguerite Duras continues to "live on" through the ongoing critical appreciation of her works…
Keywords: death; & quot; March 3; 1996& quot; Marguerite Duras; appreciation; critical analysis